STUDI LITERATUR : PENGEMBANGAN E-MODUL BERBASIS WEB DENGAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KOMPUTASI PADA MATERI PEMROGRAMAN BERORIENTASI OBYEK - Yohanes Parsaoran Selano; Leo Agung S, Sri Sumaryati (Prosiding Seminar Nasional Indonesia, 2024)
In this literature study research, it will produce preferences regarding the development of E-modules using the Research and Development (RnD) method by adopting the model from Borg and Gall, namely product design, product design, product evaluation development, web-based e-module online products, and conducting summative evaluation. This development produces an E-module for Computational Thinking Skills on Object-Oriented Programming material which is ready to be tested and can be accessed by students independently. This research is based on several educators who do not yet have the ability to provide learning media for visual or real material. The solution is to develop a learning model that requires real objects and compare previous research in e-module development with the same method. The research results show that the development of web- based e-modules with the PBL or Project Based Learning learning model shows an increase in computational thinking skills in object-oriented programming material in class X MIPA students at SMA Pradita Dirgantara located on Jl. Cendrawasih, Ngesrep, Ngemplak, Boyolali, Central Java.